CORRECTIVE MAINTENANCE ON DEFLECTOR ROLL USING BREAKDOWN METHOD AT PT PELAT TIMAH NUSANTARA (LATINUSA), TBK. - Wijaya, Ryvaldi Tyas; Notonegoro, Hamdan Akbar; Dwinanto, Dwinanto; Satria, Dhimas; Listijorini, Erny; Jannah, Miftahul (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2025)
Deflector Roll plays an essential role in the manufacturing of tinplate at PT Pelat Timah Nusantara (Latinusa), Tbk. This research examines the corrective maintenance procedure by employing the breakdown method to pinpoint repeated problems and their resolutions. The primary issues noted include degraded bearings, soiled surfaces, and uneven rollers, all of which hinder production continuity. The maintenance procedures consist of disassembling, examining, replacing, cleaning, balancing, and reassembling. Analyzing 55 documented damage occurrences from 2015 to 2024 reveals that surface-related problems were predominant, with 9 instances (16.36%) of glossy smooth surfaces, followed closely by surface buckling (14.55%) and dirty surfaces (14.55%). The outcome indicates that organized maintenance enhances efficiency and extends roll lifespan